The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3109/1547691x.2013.809038
|View full text |Cite|
|
Sign up to set email alerts
|

Immunomodulating effects and hypersensitivity reactions caused by Northeast Indian black fly salivary gland extract

Abstract: The genus Simulium, black fly (Diptera), comprises 41800 species worldwide, of which 67 species under six subgenera have been well studied in India. While at the extreme, black fly bites can cause onchocerciasis or river blindness, the majority of clinical observations indicate mainly severe pain and continuous itching at bite sites. This investigation experimentally observed that black fly salivary extract (BFSE) causes unique biologic effects including immunomodulation, anti-coagulation, and hypersensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…As vectors of disease agents (leucocytozoonosis, human onchocerciasis, mansonellosis, bovine onchocerciasis and the virus that causes vesicular stomatitis) [1], they also cause intolerable nuisances because of their abundance and habit of swarming and biting [1]. Blackflies introduce salivary molecules into the biting lesion, which are responsible for severe allergic reactions [2, 3]. In Spain, blackfly populations have expanded recently.…”
Section: Introductionmentioning
confidence: 99%
“…As vectors of disease agents (leucocytozoonosis, human onchocerciasis, mansonellosis, bovine onchocerciasis and the virus that causes vesicular stomatitis) [1], they also cause intolerable nuisances because of their abundance and habit of swarming and biting [1]. Blackflies introduce salivary molecules into the biting lesion, which are responsible for severe allergic reactions [2, 3]. In Spain, blackfly populations have expanded recently.…”
Section: Introductionmentioning
confidence: 99%
“…A blackfly bite usually causes local pain, swelling, and redness; however, the bite can also cause a systemic reaction (blackfly fever) that precipitates headaches, fever, nausea, vomiting, malaise, and generalized lymphadenopathy [ 11 , 12 ]. Blackfly salivary secretions contain a wide range of physiologically active molecules that can induce local immunomodulation and anticoagulation and local and systemic hypersensitivity reactions in humans [ 13 ]; however, patients with severe blackfly hypersensitivity reactions have rarely been reported. Orange et al [ 14 ] reported a patient with recurrent episodes of presumed cellulitis after blackfly bites who subsequently developed two episodes of delayed hypersensitivity reactions to these bites, including Guillain-Barré syndrome (GBS) and nephrotic syndrome (NS).…”
Section: Discussionmentioning
confidence: 99%
“…It is accompanied by headache, nausea, fever, and swollen lymph nodes. A severe anaphylactic reaction is a less common manifestation that may require hospitalization [61].…”
Section: Simuliidae (Blackflies)mentioning
confidence: 99%
“…Various clinical presentations are described (edematous, erythematous-edematous, erysipeloid, inflammatory-indurative, phlegmonoid, and hemorrhagic), but the itching, localized swelling, inflammation eruptions of pruritic papules, vesicles, intense pruritus, and erythematous wheals are common symptoms, resulting from a hypersensitive reaction to black fly bites [62] (Figure 2, Table 2). The Simulium dermatitis is a concern with a high risk of anaphylaxis and acute cardiotoxicity in hypersensitive individuals [61].…”
Section: Simuliidae (Blackflies)mentioning
confidence: 99%